(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article analyzes the issues of forming and developing pragmatic competence in the process of English language education among medical students. The author outlines the theoretical foundations of pragmatic competence, existing problems and methodological solutions. According to the results of the study, it was proven that when using a communicative approach, tasks based on empathy, cross-cultural comparison and innovative technologies, positive changes were observed in the speech activity of students.